Pendampingan Optimalisasi Sarana Prasarana Wisata Taman Sukosewu Dalam Upaya Meningkatkan Kepuasan Pengunjung di Desa Sukorejo - Amany, Ruhil; Witasari, Rinesti (Social Science Academic, 2024)
Several villages in Sukorejo District have the potential to become tourist villages. Tourist villages can be a focus for development and a driver of the community economy, especially in Sukorejo Village. Sukorejo Village has tourism development, one of which is Sukosewu Park tourism which is an attractive tourist destination. Requires efforts to optimize Sukosewu Park tourism activities. In efforts to develop and optimize Sukosewu Park tourism, the first thing that must be addressed is digital marketing mastery, this plays an important role as a medium for information and publication of village tourism activities. This activity was carried out to optimize the use of digital marketing by bringing in speakers from the campus world and activists to share their life stories and provide strategies for creating digital tourist attractions. This activity made youth and community leaders come up with new ideas to make Sukorejo Village more developed by utilizing local wisdom. The second thing that must be optimized is the facilities and infrastructure of Sukosewu park. The results of this mentoring activity succeeded in reaping positive responses from the first community to increase visitors. By publishing on social media you can expand your reach and attract more people to visit the park. Second, building a positive image by demonstrating commitment to developing public spaces that are beautiful and visitor friendly. Third, Improving the Local Economy. With the local economy improving, more visitors can support local businesses around the park, such as food and drink vendors. Fourth Space for Recreation. The well-maintained garden provides a pleasant and safe place to relax, gather and exercise. Fifth, improve the quality of life. Having a beautiful and comfortable park can contribute to the welfare of the community